Large metastability in Cu (In, Ga)Se2 devices: The importance of buffer properties. (26th June 2019) - Repins, Ingrid; Glynn, Stephen; Silverman, Timothy J.; Garris, Rebekah; Bowers, Karen; Stevens, Bart; Mansfield, Lorelle
Abstract: Some commercial Cu (In, Ga)Se2 (CIGS) modules show large changes in current‐voltage parameters with light soaking. While such changes are not necessarily indicative of a performance problem, the associated uncertainty may be disadvantageous in a highly competitive market. Thus, it is beneficial to understand the origin of large metastabilities in order to define what processing changes might diminish metastability without impacting other desirable aspects of high‐performance devices. This study attempts to reproduce large metastabilities like those in some commercial products both through absorber and buffer processing variations in small devices. While variations of both types were found to affect metastability, only buffer variations could reproduce large metastability in high‐efficiency devices. Device modeling confirms that buffer effects alone are sufficient to explain the large metastability seen in these devices. Abstract : Some commercial Cu(In, Ga)Se2 modules show large changes in current‐voltage parameters with light soaking. This study attempts to reproduce such large metastabilities through absorber and buffer processing variations in small devices. While variations of both types were found to affect metastability, only buffer variations could reproduce large metastability in high‐efficiency devices. Device modeling confirms that buffer effects alone are sufficient to explain the large metastability seen in these devices.